Non-glycosylated G protein with CpG ODN provides robust protection against respiratory syncytial virus without inducing eosinophilia - Kawahara, Eigo; Shibata, Takehiko; Hirai, Toshiro; Yoshioka, Yasuo (Frontiers in Immunology, 2023)
Introduction Respiratory syncytial virus (RSV) vaccines targeting the fusion glycoprotein (F protein) are highly effective clinically in preventing RSV challenges. The attachment glycoprotein (G protein) is a potentially effective vaccine antigen candidate, as it is important for cell adhesion during infection. However, vaccine-associated enhanced diseases in mice, such as eosinophilic lung inflammation following RSV challenge, are a concern with G protein vaccines. This study aimed to design an effective G protein vaccine with enhanced safety and efficacy by evaluating the efficacy and adverse reactions of vaccines composed of different recombinant G proteins and adjuvants in mice. Methods Mice were subcutaneously immunized with glycosylated G protein expressed in mammalian cells (mG), non-glycosylated G protein expressed in Escherichia coli (eG), or F protein with or without aluminum salts (alum), CpG oligodeoxynucleotide (CpG ODN), or AddaVax. After vaccination, the levels of G-specific antibody and T-cell responses were measured. The immunized mice were challenged with RSV and examined for the viral load in the lungs and nasal turbinates, lung-infiltrating cells, and lung pathology. Results mG with any adjuvant was ineffective at inducing G-specific antibodies and had difficulty achieving both protection against RSV challenge and eosinophilia suppression. In particular, mG+CpG ODN induced G-specific T helper 1 (Th1) cells but only a few G-specific antibodies and did not protect against RSV challenge. However, eG+CpG ODN induced high levels of G-specific antibodies and Th1 cells and protected against RSV challenge without inducing pulmonary inflammation. Moreover, the combination vaccine of eG+F+CpG ODN showed greater protection against upper respiratory tract RSV challenge than using each single antigen vaccine alone. Discussion These results indicate that the efficacy of recombinant G protein vaccines can be enhanced without inducing adverse reactions by using appropriate antigens and adjuvants, and their efficacy is further enhanced in the combination vaccine with F protein. These data provide valuable information for the clinical application of G protein vaccines.